Multan an Urban Center under the Muslim Rulers (From 8th Century to 15th Century): Exploring the Historical Evolution and Religious Significance of Multan (Journal of Advances and Scholarly Researches in Allied Education, 2016)
The famous metropolis of the Multan was originally situated on the Ravi. It was a walled city with a strong fortress situated on opposite banks of an old course of the Ravi which now flows between the city as well as around it.[1] Multan was known by several names but all of them referred either to God Vishnu or the Sun.